1980
DOI: 10.1111/j.1365-2672.1980.tb04718.x
|View full text |Cite
|
Sign up to set email alerts
|

Candida guilliermondii, an Actidione‐resistant Yeast from Wine*

Abstract: Candida guilliermondii var. guilliermondii, a yeast which showed high resistance to actidione, was isolated from a red wine sample. Growth in 5000 parts/106of actidione was equal to that of the control. Sorbic acid and sodium benzoate were most effective in checking the growth at 250 parts/106but growth occurred at 750 parts/106of potassium metabisulphite. Fermentation of glucose, galactose, sucrose and raffinose was not inhibited in the presence of 1000 parts/106actidione. This is the first report on the occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…It is interesting to note that the growth of another actidione resistant yeast, Candida guilliermondii var. guilliermondii was completely inhibited by sorbic acid and sodium benzoate at 250 ppm and by potassium metabisulphite at 750 ppm (Ethiraj et al, 1980b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that the growth of another actidione resistant yeast, Candida guilliermondii var. guilliermondii was completely inhibited by sorbic acid and sodium benzoate at 250 ppm and by potassium metabisulphite at 750 ppm (Ethiraj et al, 1980b).…”
Section: Resultsmentioning
confidence: 99%
“…No other genus has been shown to be resistant to actidione. However, a recent report from our laboratory (Ethiraj et al, 1980b) showed that Candida guilliermondii vat. guillierrnondii which had been isolated from a red wine sample showed resistance up to 5000 ppm.…”
Section: Introductionmentioning
confidence: 92%